1981
DOI: 10.1002/bjs.1800680615
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in patients undergoing maintenance haemodialysis and renal transplantation

Abstract: The difficulty in diagnosis of tuberculosis in patients with chronic renal failure or on immunosuppressive therapy is discussed. Anti-tuberculous therapy was required in 19 out of 315 patients who received a renal transplant in the Urology Unit, Hammersmith Hospital, between February 1961 and December 1979. Twelve patients were from overseas. Their management and the effect of anti-tuberculous therapy on the immunosuppressed patient were also studied. The disease was treated successfully in 18 patients, even t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The differences are still greater when the estimated incidence in special groups is considered (renal transplant patients 1986, hemodialysis patients 847, CAPD patients 4210 per 100,000 population annually). Other authors have reported that the risk of developing mycobacteriosis in patients with chronic renal failure is 10 to 15 times greater than that in the normal population (2,3,4,6,7). One study on renal transplant recipients from several US institutions reported an estimated annual incidence of 480 to 530 cases per 100,000 population, compared with a national annual incidence of 13 per 100,000 population (8).…”
Section: Patients In Whom Mycobacteriurn Tuberculosismentioning
confidence: 95%
“…The differences are still greater when the estimated incidence in special groups is considered (renal transplant patients 1986, hemodialysis patients 847, CAPD patients 4210 per 100,000 population annually). Other authors have reported that the risk of developing mycobacteriosis in patients with chronic renal failure is 10 to 15 times greater than that in the normal population (2,3,4,6,7). One study on renal transplant recipients from several US institutions reported an estimated annual incidence of 480 to 530 cases per 100,000 population, compared with a national annual incidence of 13 per 100,000 population (8).…”
Section: Patients In Whom Mycobacteriurn Tuberculosismentioning
confidence: 95%
“…Our experience suggests that at least 3-6 months of treatment should be provided prior to renal transplantation and that treatment should be continued following transplantation. McWhinney et al [12] reported 4 patients who also underwent antituberculosis treatment prior to and after renal transplantation with no reactivation following transplantation. The other reports on tuberculosis in RT patients have not addressed this issue [2, 5-8, 10, 11, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Since ESRD and RT patients are susceptible to infections, it is inevitable that the prevalence of M. tuberculosis in this population is going to increase. Mycobacterial infection, although suggested by many to be common in HD patients, has seldom been reported in the literature prior to 1996 and most reports have described a small number of cases [8][9][10][11][12]. In the past 2 years 5 reports have emerged from developing countries suggesting either a resurgence or greater recognition of this infection [1,2,[4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…9 The clinical features of TB can be unusual, and may be masked because of the blunted response to infection. 4,7,8 In addition, extrapulmonary lesions are more frequent in patients following transplantation compared to patients without immunosuppression. 8,9 Disseminated TB is common in renal transplant patients, accounting for 40% of cases, 9 in marked contrast to the 0.6%-1.4% incidence in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…4 Earlier reports emphasized the rarity of tuberculosis (TB) in these patients, 5,6 however, more recent ones have documented high incidence of TB in renal transplant recipients. 7,8 Qunibi et al 8 noted the presence of TB in 14 of 403 renal transplant recipients operated over a nine-year period, giving an incidence rate of 3.5%. On reviewing the literature, Singh et al 9 found 437 cases of TB in renal transplant recipients.…”
mentioning
confidence: 99%